Der vorzeitige Blasensprung: Eine anhaltende Herausforderung in der Perinatalmedizin? - Gortner, L. (Klinische Pädiatrie, 2016)
Two recently published observational studies have focused on the outcome of very preterm respectively of very low birth weight infants after preterm premature rupture of fetal membranes (PPROM). One single center study from the Netherlands enrolling 160 women with PPROM before 24 weeks gestational age, who admitted to the Rotterdam Medical Center between 2002 and 2011, were analyzed 14. In parallel, there was a publication from the German Neonatal Network (GNN) enrolling about 6,000 very low birth weight infants, whose data were analyzed under the aspect of PPROM as a potential risk factor for adverse neonatal outcomes 5.